Transformation of polyhedrons. (1st May 2018) - Chen, Yan; Yang, Fufu; You, Zhong
Abstract: Polyhedral transformation enables large volumetric change amongst Platonic and Archimedean solids. It has great potential in applications where transportability and protection of payload are critical design features, e.g., small or micro satellites, space habitats or planetary rovers. However, existing designs introduce many degrees of freedoms, making the control of transformation process extremely difficult and cumbersome, and thus the practical applicability of the mechanisms is restricted. This paper develops a kinematic method to enable polyhedral transformation with a single degree of freedom. The approach has been implemented for the transformation between truncated octahedron and cube. Motion analysis indicates that transformation path is unique without singularity, which is further demonstrated with physical validation models. We envisage that our method could be suitable for extension to other paired polyhedron sets.